2015
DOI: 10.1371/journal.pone.0126662
|View full text |Cite
|
Sign up to set email alerts
|

Community Phylogenetics: Assessing Tree Reconstruction Methods and the Utility of DNA Barcodes

Abstract: Studies examining phylogenetic community structure have become increasingly prevalent, yet little attention has been given to the influence of the input phylogeny on metrics that describe phylogenetic patterns of co-occurrence. Here, we examine the influence of branch length, tree reconstruction method, and amount of sequence data on measures of phylogenetic community structure, as well as the phylogenetic signal (Pagel’s λ) in morphological traits, using Trichoptera larval communities from Churchill, Manitoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 49 publications
3
42
1
Order By: Relevance
“…Sequences under 500 base pairs were omitted from the final analysis, leaving 1,314 sequences. Our approach was based on the findings of Boyle and Adamowicz (), who investigated the utility of COI data for estimating phylogenetic community structure. They found that, in general, COI data will estimate the relative genetic distances between pairs of co‐occurring species very well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences under 500 base pairs were omitted from the final analysis, leaving 1,314 sequences. Our approach was based on the findings of Boyle and Adamowicz (), who investigated the utility of COI data for estimating phylogenetic community structure. They found that, in general, COI data will estimate the relative genetic distances between pairs of co‐occurring species very well.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, phylogenies derived from single loci will always be subject to chance events and biases (Pamilo & Nei, 1988). Therefore, Boyle and Adamowicz (2015) recommended the use of an enforced backbone phylogeny-especially when dealing with data collected at a broader geographic scale and across more diverse taxonomic levels. Thus, we provided two sources of a priori information for the Bayesian analysis.…”
Section: Phylogenetic Datamentioning
confidence: 99%
“…However, animal barcode data can increase the taxon density in a phylogenetic study when 'backbone' phylogenies constructed using multi-gene data or phylogenomics approaches constrain the deeper topology (e.g. genus or family-level relationships; see Trunz et al, 2016), in combination with barcode data, which are available for more species (Wilson, 2011;Boyle & Adamowicz, 2015). By incorporating barcode markers, phylogenetic trees have better phylogenetic resolution, which can yield more precise conclusions regarding community structuring and processes (Kress et al, 2009;Pei et al, 2011;Davies et al, 2012).…”
Section: Specialization Questionmentioning
confidence: 99%
“…To constrain deep phylogenetic nodes and follow broadly accepted phylogenetic patterns, supertree methods (Bininda‐Emonds & Sanderson, ; Webb & Donoghue, ) can be combined with DNA barcode sequence data (Erickson et al, ; Kress et al, ) to provide more accurate depictions of topology. Furthermore, the incorporation of a backbone phylogeny can provide more accurate estimates of the branch lengths (Boyle & Adamowicz, ) and potentially affect the metrics of phylogenetic community diversity (Swenson, ). Since ecological and evolutionary processes might operate at different phylogenetic depths (Mazel et al, ), it seems reasonable that phylogenetic diversity metrics that are sensitive to processes operating at deep phylogenetic depths may be strongly influenced by combining supertree methods with DNA barcode sequence data, whereas those estimates that are largely capturing diversity at the tips of the phylogeny may be less influenced, although this remains to be tested.…”
Section: Introductionmentioning
confidence: 99%